New realms of bioscience research in Africa - International Livestock Research Institute (International Livestock Research Institute, 2012)
Charles Masembe from Uganda is one of the recipients of the competitive Africa Biosciences Challenge Fund fellowships. Through this fund, he was able to gain access to the Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI) Hub in Nairobi and conduct his studies on African swine fever utilising equipment and skills that he would not have access to otherwise.